PENGGUNAAN AKRONIM BAHASA MELAYU MANADO DI SMP NEGERI 8 MANADO PROVINSI SULAWESI UTARA - Loindong, Pamela C. (Kajian Linguistik, 2017)
This research focused on the micro linguistic, where the object of study is on the morphology associated with the use of acronym of Bahasa Melayu Manado in SMP Negeri 8 Manado and was also associated with linguistic macro, focusing on sociolinguistics that will investigate the differences in age, sex and social interaction that led to the development, changes and differences in the use of acronyms, for both the teachers and students at SMP Negeri 8 Manado.The results showed that of the 104 acronyms found in SMP Negeri 8 Manado, 103 of which are in accordance with the theory of Kridalaksana (2009), McCully, Holmes (1988) and Hartanto. The acronym classification consists of an acronym formed from two words, three words, four words and five words. Based on the formation process there are 30 process of formation of new acronyms outside Kridalaksana theory. While the sociolinguistic factors based on Peter Trudgil’s theory leads to differences in the use of the acronym in Bahasa Melayu Manado among teachers and students at SMP Negeri 8 Manado are ages, situations and interactions.Keywords: acronym, forms, sociolinguistic factors